Circulating Monocytes, Tissue Macrophages, and Malaria - (:unkn) unknown (HINDAWI LTD, 2019)
Malaria is a significant cause of global morbidity and mortality. The Plasmodium parasite has a complex life cycle with mosquito, liver, and blood stages. The blood stages can preferentially affect organs such as the brain and placenta. In each of these stages and organs, the parasite will encounter monocytes and tissue-specific macrophages-key cell types in the innate immune response. Interactions between the Plasmodium parasite and monocytes/macrophages lead to several changes at both cellular and molecular levels, such as cytokine release and receptor expression. In this review, we summarize current knowledge on the relationship between malaria and blood intervillous monocytes and tissue-specific macrophages of the liver (Kupffer cells), central nervous system (microglia), and placenta (maternal intervillous monocytes and fetal Hofbauer cells). We describe their potential roles in modulating outcomes from infection and areas for future investigation.
Keywords: PLASMODIUM-FALCIPARUM INFECTION; CYTOKINE PRODUCTION; PLACENTAL MALARIA; PHAGOCYTIC-CELLS; DENDRITIC CELLS; T-CELLS; ACTIVATION; IMMUNE; STAGE; WOMEN